Gestión administrativa financiera y su incidencia en el control presupuestario técnico y sanitario del hospital general Quevedo periodo 2020, plan de mejoramiento. - Vergara Vera, Yury Maryury (2021)
The objective of this research project is to evaluate the financial administrative management and its impact on the technical and health budgetary control of the Quevedo General Hospital, a public entity that is located in the Quevedo canton, this work was carried out through a situational diagnosis in the processes of the administrative departments and the medical area, it was developed using the methodology of the interviews with all the personnel involved in the preparation of the annual proforma. In the results there were problems in the fulfillment of the planning, causing new reprogramming and complying with a budget execution of $19,262,874.15, in the cost groups 510,000, 530000, 570000 and 990000, which corresponds to 83.65% compared to the codified budget, for what is recommended to avoid financial reprogramming and recurrent budgetary modifications. In addition, an adequate preparation and publication of the contracting processes according to the months programmed in the PAC, observing the execution times, delivery times and corresponding payments, in order to avoid unpaid processes that affect the annual budget execution and are considered as debts in subsequent fiscal years, in addition this research contains the Contextual Research Framework, Theoretical Framework, Research Methodology, Administrative Proposal and Administrative Framework, which allows at the end of the project to help take measures to improve budget execution. Keywords: Administrative Management, Planning, Budget Execution